Predictive Motor Timing and the Cerebellar Vermis in Schizophrenia: An fMRI Study - Lošák, Jan; Hüttlová, Jitka; Lipová, Petra; Marecek, Radek; Bareš, Martin; Filip, Pavel; Žubor, Jozef; Ustohal, Libor; Vanícek, Jirí; Kašpárek, Tomáš (Schizophrenia bulletin, 2016)
Abnormalities in both time processing and dopamine (DA) neurotransmission have been observed in schizophrenia. Time processing seems to be linked to DA neurotransmission. The cognitive dysmetria hypothesis postulates that psychosis might be a manifestation of the loss of coordination of mental processes due to impaired timing. The objective of the present study was to analyze timing abilities and their corresponding functional neuroanatomy in schizophrenia. We performed a functional magnetic resonance imaging (fMRI) study using a predictive motor timing paradigm in 28 schizophrenia patients and 27 matched healthy controls (HC). The schizophrenia patients showed accelerated time processing compared to HC; the amount of the acceleration positively correlated with the degree of positive psychotic symptoms and negatively correlated with antipsychotic dose. This dysfunctional predictive timing was associated with BOLD signal activity alterations in several brain networks, especially those previously described as timing networks (basal ganglia, cerebellum, SMA, and insula) and reward networks (hippocampus, amygdala, and NAcc). BOLD signal activity in the cerebellar vermis was negatively associated with accelerated time processing. Several lines of evidence suggest a direct link between DA transmission and the cerebellar vermis that could explain their relevance for the neurobiology of schizophrenia.
Keywords: dospělí; Magnetic Resonance Imaging; vermis cerebelli; Female; Brain Mapping; nervová síť; Adult; ženské pohlaví; pohybová aktivita; lidé; Nerve Net; magnetická rezonanční tomografie; vnímání času; Cerebellar Vermis; mapování mozku; mozek; schizofrenie; Male; Brain; Time Perception; Schizophrenia; Motor Activity; mužské pohlaví; Humans